KONSTRUKSI PERLINDUNGAN HUKUM UNTUK PEMBELI TANAH BERITIKAD BAIK: ANALISIS DAN SOLUSI PRAKTIS - opan satria (Jurnal Hukum Lex Generalis, 2024)
Purchasing land is one of the transactions that carries a high risk in Indonesia, especially related to the legality and ownership of the land. Land buyers who have good intentions are often faced with various complex legal issues that have the potential to harm them. Therefore, legal protection for buyers who have good intentions is crucial to guarantee security and legal certainty in these transactions. This research aims to examine in depth the concept of Good Faith in determining land rights and explore the views of judges regarding buyers of land rights who have good intentions. The approaches used are the Legislative Approach, Conceptual Approach and Interpretation Approach. The results and findings show that there are several main legal risks in purchasing land. Firstly, the validity of documents is often a big problem, with many well-meaning land buyers getting stuck with invalid or fake documents. Careful examination of legal documents such as land certificates, permits, and proof of ownership is very important to ensure the validity of transactions. Second, ownership disputes often occur, where land purchased by buyers with good intentions turns out to be the object of dispute due to overlapping ownership claims or heir disputes. Although existing laws and regulations are designed to protect buyers in good faith, research shows that their implementation in practice is still less than effective. To minimize legal risks, it is important to carry out thorough due diligence before carrying out a land purchase transaction, including checking the history of the land, the validity of the documents, and the legal status of the land both in relation to physical data and juridical land data. To reduce this risk, buyers are advised to use professional services such as notaries and lawyers who are experienced in land transactions.